2007
DOI: 10.1089/end.2007.9876
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Laparoscopic Pyeloplasty: 4-Year Experience

Abstract: Our series of patients undergoing laparoscopic pyeloplasty had excellent results with low morbidity. We consider this our primary technique for surgical correction of UPJO in patients older than 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Postoperatively, one child had a urinary tract infection that necessitated hospital admission and administration of intravenous antibiotics. Similarly, Lam et al [14] reported on 28 children who underwent laparoscopic dismembered pyeloplasty. One child required hospitalization longer than 23 h because of postoperative ileus.…”
Section: Discussionmentioning
confidence: 95%
“…Postoperatively, one child had a urinary tract infection that necessitated hospital admission and administration of intravenous antibiotics. Similarly, Lam et al [14] reported on 28 children who underwent laparoscopic dismembered pyeloplasty. One child required hospitalization longer than 23 h because of postoperative ileus.…”
Section: Discussionmentioning
confidence: 95%
“…[1923] In a recently published study of transperitoeal LP in children, 28 out of 29 were completed successfully and mean operative time was 255 min (range 157-396), mean estimated blood loss 10 ml in all. [21] Similarly, in other studies of transperitoneal LP in children, 16 out of 16 were completed successfully and mean operative time was 160 min (range 90-270), mean estimated blood loss was 60 ml (range not given) and mean hospital stay was not reported,[19] mean operating time was 219 min (range 140-310) with a mean hospital stay of 2.4 days (range 1-5) and 2/22 (9%) required conversion to open surgery. [23] Majority of the cases with higher blood loss were during the initial part of the series (learning curve effect).…”
Section: Discussionmentioning
confidence: 99%
“…Except for a longer operative time, the results have been comparable with those of open repair, even in infants [5,6,12,13]. Although considered technically demanding, the retroperitoneal approach has been preferred by some surgeons because of better tolerance of potential urinary leakage into the retroperitoneal space and a lower risk of injury to intraperitoneal organs [9,10,11].…”
Section: Introductionmentioning
confidence: 88%